2022
DOI: 10.3389/fcvm.2022.724262
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Long Non-coding RNA LINC01480 Is Associated With Immune Infiltration in Coronary Artery Disease Based on an Immune-Related lncRNA-mRNA Co-expression Network

Abstract: Coronary artery disease (CAD) is considered one of the leading causes of death worldwide. Although dysregulation of long non-coding RNAs (lncRNAs) has been reported to be associated with the initiation and progression of CAD, the knowledge regarding their specific functions as well their physiological/pathological significance in CAD is very limited. In this study, we aimed to systematically analyze immune-related lncRNAs in CAD and explore the relationship between key immune-related lncRNAs and the immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…On the other hand, 508 RCC samples from TCGA were filtered out by a clinical follow-up time of more than 30 days, and the sample labeled ‘01A’ in the dataset was used for the univariate COX analysis. (Liu et al 2022; Xiong et al 2022)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, 508 RCC samples from TCGA were filtered out by a clinical follow-up time of more than 30 days, and the sample labeled ‘01A’ in the dataset was used for the univariate COX analysis. (Liu et al 2022; Xiong et al 2022)…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, 508 RCC samples from TCGA were filtered out by a clinical follow-up time of more than 30 days, and the sample labeled '01A' in the dataset was used for the univariate COX analysis. (Liu et al 2022;Xiong et al 2022) Genes with p <0.001 in univariate COX analysis were retained and further subjected to LASSO-penalized COX analysis with lambda 100. Subsequently, five genes were retained and subjected to a multivariate COX analysis.…”
Section: Establishment Of a Risk Assessment Modelmentioning
confidence: 99%
“…13,14 Another study has confirmed that exosomal lncRNA acts as a potential diagnostic and prognostic biomarker for GC. 12 LINC01480, a kind of lncRNA, is closely related to immune infiltration in coronary artery disease, 15 while its roles in GC development remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating pieces of evidence have demonstrated that lncRNAs participate in the occurrence and development of GC by regulating cell proliferation, invasion, migration, and metastasis. , Another study has confirmed that exosomal lncRNA acts as a potential diagnostic and prognostic biomarker for GC . LINC01480, a kind of lncRNA, is closely related to immune infiltration in coronary artery disease, while its roles in GC development remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Kushnareva et al found that the expression of PD-L1 and the number of CD3+ cells in endothelial cells increased in the myocardium of patients with ischemic heart failure (11). Besides, several bioinformatic comprehensive analyses have also confirmed the difference in immune infiltrates between patients with coronary artery disease and healthy controls (12,13). However, the mechanisms underlying immune infiltration in ICM remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%